Neurocognitive performance predicts treatment outcome with cognitive behavioral therapy for major depressive disorder. (November 2018) - Metts, Allison V.; Keilp, John G.; Kishon, Ronit; Oquendo, Maria A.; Mann, J. John; Miller, Jeffrey M.
Highlights: Neuropsychological test performance predicted remission to CBT for depression. Remitters showed worse baseline neurocognitive performance than non-remitters. Remitters showed lower values Continuous Performance Test d' values. CBT may benefit individuals with mild cognitive difficulties during a depressive episode. Abstract: The current study examined the contribution of baseline neuropsychological functioning to the prediction of antidepressant outcome with cognitive behavioral therapy (CBT) for Major Depressive Disorder (MDD). We hypothesized that depressed participants who were more neurocognitively intact and had less rigid, negative thinking would respond better to CBT. Thirty-one MDD patients completed a comprehensive neuropsychological battery before initiation of CBT. A subgroup also completed a probabilistic reversal learning task. Depression severity was assessed with the Beck Depression Inventory (BDI); rigid, negative thinking was assessed with the Dysfunctional Attitudes Scale (DAS) and the Automatic Thoughts Questionnaire (ATQ) throughout treatment. Remitters were compared to non-remitters. Paradoxically, eventual remitters performed generally worse across the neuropsychological battery considered as a whole. Univariate testing showed a significant difference on only a single measure, the Continuous Performance Test d', when corrected for multiple comparisons. Baseline rigid, negative thinking did not predict treatment outcome. Results suggest that the structure of CBT may particularly benefit individuals with mild depression-related neurocognitive difficulties during a depressive episode. Further research is needed to examine these patient characteristics and their potential contribution to the mechanisms of CBT efficacy.